Mobile Dictionary For Hitu Ethnic Language - Nurlete, Fauzan Yuusril; Fatkhurohman, Agus (Universitas Ahmad Dahlan, 2021)
Indonesians have many diverse ethnic groups. Each tribe has different traditions and cultures. As with language, each tribe has a different local language to communicate and interact with their community and environment. Hitu is one of the villages (Negeri) on Ambon Island, Central Maluku Regency. People in Tanah Hitu communicate every day using the Hitu language. Hituese is one of the local languages in Indonesia. The Hitu Country dictionary application is a mobile-based application that can make it easier for the people of Hitu Village to find translations from Hitu - Indonesian - English or vice versa. This is because many foreign and domestic tourists visit Hitu Village. People in Hitu can certainly speak Indonesian, but not all are able to speak it fluently. Therefore, this dictionary was created to facilitate the community in Hitu. This mobile application can display vocabulary translations that can be searched from Hitu to Indonesian and Indonesian to Hitu or vice versa. This dictionary will use Android-based mobile devices and will also take advantage of current developments that are very sophisticated. The Hitu dictionary application will be easy to carry anywhere and can be accessed every day.